State paid family leave policies and breastfeeding duration: cross-sectional analysis of 2021 national immunization survey-child - Julia Rosenberg; Deanna Nardella; Veronika Shabanova (BMC, 2024)
Abstract Background Paid parental leave policies may promote breastfeeding, which can have short- and long-term health benefits for both members of the birthing person-infant dyad. In the United States, where 56% of the workforce qualifies for unpaid federal medical leave, certain states have recently enacted paid parental and family leave policies. We aimed to assess the extent to which living in states with versus without paid family leave was associated with feeding regimens that included breastfeeding. Methods In this cross-sectional analysis of the 2021 National Immunization Survey-Child, we assessed feeding outcomes: (1) exclusively breastfed (only fed breastmilk-never infant formula-both before and after six months of age), (2) late mixed breastfeeding (formula after six months), (3) early mixed breastfeeding (breastfed, formula before six months), and (4) never breastfed. We conducted Pearson χ2 to compare social-demographic characteristics and multivariable nominal regression to assess extent to paid family leave was associated with breastfeeding regimens, compared with never breastfeeding. Results Of the 35,995 respondents, 5,806 (25% of weighted respondents) were from states with paid family leave policies. Compared with never breastfeeding, all feeding that incorporated breastfeeding-exclusive breastfeeding, late mixed feeding (breastfed, formula introduced after six months), and early mixed feeding (breastfed, formula introduced before six months)-were more prevalent in states with paid family leave policies. The adjusted prevalence ratio (aPR) and differences in adjusted prevalence compared with never breastfeeding in states with versus without paid family leave policies were: aPR 1.41 (95% CI 1.15, 1.73), 5.36% difference for exclusive breastfeeding; aPR 1.25 (95% CI 1.01, 1.53), 3.19% difference for late mixed feeding, aPR 1.32 (95% CI 1.32, 1.97), 5.42% difference for early mixed feeding. Conclusion States with paid family leave policies have higher rates of any breastfeeding and of exclusive breastfeeding than states without such policies. Because all feeding types that incorporate breastfeeding were higher in states with paid family leave policies, expansion of paid family leave may improve breastfeeding rates.